O efeito da suplementação crônica com vitamina d sobre a obesidade hipotalâmica e o controle secretor de insulina - Guareschi, Zoé Maria Neves de Carvalho (2018)
Vitamin D (VD) is known to play a role in bone metabolism. VD receptors (VDRs) in adipose tissue and endocrine pancreas demonstrate the action of VD on energy homeostasis. The accumulation of adipose tissue promotes insulin resistance (IR), breaking the glycemic and lipid homeostasis, initially overcome by hypersecretion of insulin by beta (β) pancreatic cells. This study evaluated the effect of chronic VD supplementation on hypothalamic obesity and insulin secretory control of obese rats-MSG. After rodents birth, 6 male pups per rat were kept. Half of the offspring (n = 30) were induced to obesity by application of monosodium glutamate (MSG, 4g / kg) in the neonatal phase. Controls (CON; n = 30) received equimolar saline. Weaning occurred at 30 days, half of each group (n = 15; n = 15) was supplemented with VD (12μg / kg) in corn oil (vehicle). Animals not supplemented (NS) received only vehicle. Four experimental groups (n = 15 / group) were formed: CON-NS; CON-VD; MSG-NS; MSG-VD. At 90 days the animals were euthanized and the fat deposits were collected. Part of the pancreatic islets were isolated and incubated in the presence of glucose (5.6 and 8.3 mM). The cholinergic response was evaluated in the presence of glucose + carbachol (CCh, 10μM). The other part of the pancreatic islets were isolated and transferred to protein extraction buffer for analysis of muscarinic receptor (RM3), protein kinase A (PKA) and protein C kinase (PKC) by Western blotting. The total pancreas was submitted to histology for analysis of the number and area of the pancreatic islets. Whole blood was collected, plasma used for dosages of glucose, cholesterol, triglycerides and insulin. Data expressed as mean ± standard error of the mean, evaluated by Anova-2 way and post Tukey test (p <0.05). At the end, it was observed that body weight and CNA were lower in the MSG-NS group than in the CON-NS group (31.57% and 12.47%, respectively). Highest mean weight of subcutaneous fat (188.31%) and visceral fat (47.63%), comparing mean MSG-NS with CON-NS. The glycemic mean was significantly higher in the MSG-NS (78.29%) and MSG-VD (48.81%) groups compared to the CON-NS group. Animals from the MSG-VD group had lower mean (86.76%) insulin, compared to the MSG-NS group. Supplemented animals presented lower mean triglycerides (50.40%) than those in the MSG-NS group. Cholesterol was higher (33.58%) in MSG-VD animals compared to MSG-NS animals. Treatment with MSG impaired insulin sensitivity and was improved by VD. HOMA-IR was higher in animals of the MSG-NS group than in the other experimental groups, decreased by VD in MSG-VD animals (89.81%), compared to the MSG-NS group. MSG-NS rodent islets decreased cholinergic effect, with no significant differences in RM3, PKA and PKC expression. The number of pancreatic islets was not altered; however, pancreatic islets of MSG-VD rodents were smaller than those of the MSG-NS group. Supplementation with VD in obese rodents may reduce hypertriglyceridemia, hyperinsulinemia, and improve insulin sensitivity; the reduction of the cholinergic insulinotropic effect in the islets of MSG-VD rodents may contribute to the reduction of plasma insulin.